« Je suis un catholique » : la mémoire spirituelle de Flaubert chez les critiques chrétiens de l’entre-deux-guerres - Marina Girardin (Flaubert: Revue Critique et Génétique)
Considered as a major moment in the history of Flaubert’s studies because of the debate which opposes Proust to Thibaudet, the interwar period is marked by the discussions issued from the commemorations in honor of the century of Flaubert’s birth while reviving and extending the debate initiated by Gide and his detractors about the connection between literature and religion. From Charles du Bos to Henri Guillemin, including Albert Thibaudet and François Mauriac, the articles that we have considered in this study constitute a collection of texts which correspond to one another and which, beyond the thorny question of the finality of Flaubert’s asceticism, are supported by the peculiar will to reshape Flaubert’s spiritual memory in order to restore a new image of a christian writer to posterity.